SOME FACTORS RELATED TO TREATMENT OUTCOMES OF LUMBAR HIP SYNDROME USING ELECTRO-ACUPUNCTURE COMBINED WITH MASSAGE AND NGUYEN VAN HUONG’S PHYSICAL EXERCISES - Trần Thị Minh, Quyên; Vũ , Việt Hằng (Tạp chí Y học Quân sự, 2025)
Objectives: To describe some factors related to the outcomes of treating lumbar hip syndrome using electro-acupuncture combined with massage and Nguyen Van Huong’s exercises. Subjects and methods: A cross-sectional interventional study was conducted on 30 patients with lumbar hip syndrome caused by lumbar disc herniation. Patients were treated with electro-acupuncture combined with massage and Nguyen Van Huong’s exercises at the Traditional Medicine Clinic, Hanoi Heart Hospital, from July 2021 to September 2022. Treatment outcomes were evaluated based on changes in pain (VAS), lumbar spine flexibility (Lasegue’s test), and quality of life (Oswestry Disability Index), classified into four levels: good, fair, moderate, and poor. Results: Patients with a disease duration of less than 6 months and single-level disc herniation had significantly better treatment outcomes compared to those with disease duration of 6 months or more and multi-level herniation (p < 0.05). No significant associations were found between treatment outcomes and factors such as age, gender, occupation, or degree of disc herniation. Conclusions: Duration of disease and number of herniated disc levels are related to treatment outcomes in patients with lumbar hip syndrome due to disc herniation.